Impact of chemical reactions in snow cover on content of atmosphere over western coastal Antarctica - V. I. Bogillo; M. S. Bazylevska (Ukrainian Antarctic Journal, 2006)
It has been shown that high enrichment coefficients in comparison with current atmospheric level are characteristic for N2O, CH2=CHCH3, CO2, CH3Cl, C2H5Cl, CH2=CHCl, CH3Br, CH2Br2, CHBr3, CH3I, C2H5I, CH2=CHI, COS, CS2, CH3SSCH3 and CH3SCH3 which identified in young and aged layers of retreated glacier in West coastal Antarctica. This suggests the natural sources of their formation. Possible mechanisms of their formation from organic matter in snow cover have been discussed. The fluxes of these impurities can affect the ecosystems, chemical content of the atmosphere and cloud formation over coastal Antarctica.